2016
DOI: 10.1039/c5rp00159e
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom modules for large enrollment general chemistry courses: a low barrier approach to increase active learning and improve student grades

Abstract: In the face of mounting evidence revealing active learning approaches result in improved student learning outcomes compared to traditional passive lecturing, there is a growing need to change the way instructors teach large introductory science courses. However, a large proportion of STEM faculty continues to use traditional instructor-centered lectures in their classrooms. In an effort to create a low barrier approach for the implementation of active learning pedagogies in introductory science courses, flippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 18 publications
5
136
0
3
Order By: Relevance
“…Academic success of the students improved in the research conducted on LEGO-LOGO practices (Barker and Ansorge, 2007;Strawhacker and Bers 2015). Similarly, in the studies conducted by using FC Model, the difference in academic success of the students in the test group was statistically significant in comparison to the students in the control group and was in the favor of the test group (Eichler and Peeples, 2016;Hsieh and others, 2016;Turan, 2015). Therefore, it is thought that LEGO-LOGO practices to be carried out in FC or a class setting face-to-face contributes to improve student success.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Academic success of the students improved in the research conducted on LEGO-LOGO practices (Barker and Ansorge, 2007;Strawhacker and Bers 2015). Similarly, in the studies conducted by using FC Model, the difference in academic success of the students in the test group was statistically significant in comparison to the students in the control group and was in the favor of the test group (Eichler and Peeples, 2016;Hsieh and others, 2016;Turan, 2015). Therefore, it is thought that LEGO-LOGO practices to be carried out in FC or a class setting face-to-face contributes to improve student success.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…LEGO-LOGO uygulamaları ile ilgili olarak yapılan araştırmalarda öğrencilerin akademik başarılarının arttığı görülmüştür (Barker ve Ansorge, 2007;Özdoğru, 2013;Strawhacker ve Bers 2015). Benzer şekilde TYES Modeli kullanılarak gerçekleştirilen çalışmalarda da deney grubundaki öğrencilerin akademik başarılarının kontrol grubundaki öğrencilere göre istatistiksel olarak anlamlı farklılığa sahip ve deney grubu lehine olduğu görülmüştür (Eichler ve Peeples, 2016;Farah, 2014;Hsieh ve diğerleri, 2016;Turan, 2015). Dolayısıyla TYES ortamı ya da sınıf ortamında yüz yüze gerçekleştirilecek LEGO-LOGO uygulamalarının öğrenci başarısının artmasına katkı sağladığı düşünülmektedir.…”
Section: Sonuç Ve Tartışmaunclassified
“…Group collaboration can be formed in various learning contexts such as classroom‐based learning, computer‐based learning, game‐based learning and e‐learning. Eichler and Peeples () reported that conducting collaborative problem‐solving activities in the class has good potential for improving students’ learning outcomes. Moreover, Fu, Wu, and Ho () indicated that competition was the best learning strategy when students collaborated within groups and competed between groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Class time then establishes an interactive learning environment where students engage in activities and problem-based learning that are instructor led [5]. Flipped learning has been widely applied in STEM subjects, notably in the delivery of physics, engineering, and mathematics [3,4,8], and its use in chemistry teaching is increasing, with various studies being published on the delivery of organic or general chemistry in this way [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%